TOXCITY OF SECOND GENERATION ANTICOAGULANTS AGAINST FIELD AND COMMENSAL RODENTS - SAXENA, Y.; SAHİN, KAVİKTİTA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Investigations were carried out to evaluate the comparative efficacy of difethialone and flocoumasen against field and domestic rodents. The results reveal difethialone (0.005%) was found more effective than flocoumasen (0.005%) in managing field and domestic rodents. Percent control success was 92.8 and 94.6 with difethialone, while 88.6 and 92.20 with flocoumafen respectively in field and houses.